Gradient Accumulation Effects on mT5 Inference Performance in Zero-Shot Cross-Lingual Transfer - Assignee Research (Assignee Research, 2026)
Multilingual BERT (mBERT), a language model pre-trained on large multilingual corpora, has impressive zero-shot cross-lingual transfer capabilities and performs surprisingly well on zero-shot POS tagging and Named Entity Recognition (NER), as well as on cross-lingual model transfer. At present, the mainstream methods to solve the cross-lingual downstream tasks are always using the last transformer layer's output of mBERT as the representation of linguistic information. In this work, we explore t
Machine-generated literature synthesis.